MODERNISME DALAM TAFSIR TRADISIONALIS: (Nuansa Tafsir ‘Ilmī dalam Tafsīr al-Ibrīz Karya Bisri Musthafa) - Moh Mufid Muwaffaq (Institut Agama Islam Negeri (IAIN) Keiri, 2020)
Al-Ibrīz li Ma’rifati Tafsīr al-Qur’ān al-‘Azīz by a traditionalist KH Bisri Musthafa has numerous scientific-nuanced interpretations, a nuance that is basically typical to modernist camp. Taking some examples, this article finds that Kiai Bisri engage scientific narratives in his exegesis under a condition that they also exist in the literatures of faithful (mu’tabara) tafsīr works for Sunnites. The examples show that the tafsir works of Muḥammad b. Aḥmad al-Qurṭubī and Fakhr al-Dīn alRāzī are likely to be the main sources for Kiai Bisri. When engaging scientific narratives, Kiai Bisri aims at showing the complexity result in the amazement in the readers’ psychology. It is noteworthy that unlike other mufasir engaging ‘ilmī narratives, Kiai Bisri did not want to respond to the Westerners and marginalize traditionalist exegetes. He rather wanted to contextualize Islamic teachings. In doing so, he drew a sort of corridor basing on Sunnite teachings. This explains why he cited more al-Rāzī, an exegete characterized by the openness toward philosophy and thus any kind of development. This also explains Kiai Bisri’s fatwas (on women’s issues, for example) that is in traditional way but at the same time it is also progressive.